Economics of Endogenous Technical Change in CGE Models - The Role of Gains from Specialization - Florentine Schwark (ETH Zurich, CER-ETH - Center of Economic Research, 2010)
Computable general equilibrium models simulate the reaction of industries on carbon taxes. Their results differ strongly on the assumption of the underlying technologies. This paper compares two models and emphasizes the differences between their approaches to technology. The first model is the CITE model, which is the first model with endogenous growth based on gains from specialization so that growth dynamics result from investment incentives. The second model is a model with exogenous growth of endowments, which is the basis for many other CGE models. The results show that the CITE model unveils dynamics that cannot be obtained with the model based on exogenous growth. Reactions are stronger in the CITE model and industries need more time to approach the new balanced growth path.
Keywords: Q54; C63; O41; Q43; Q56; 330; Endogenous growth; gains from specialization; CGE models; energy policy; Technischer Fortschritt; Internationale Arbeitsteilung; Allgemeines Gleichgewicht; Endogenes Wachstumsmodell